Emergence of organizational routines in entrepreneurial ventures. Issue 3 (7th August 2017) - Lin, Haifen; Murphree, Michael; Li, Sali
Abstract : Purpose: The purpose of this paper is to expand the understanding of the process by which organizational routines emerge in entrepreneurial ventures. The emphasis is on the role of management and interaction in shaping shared schemata among members of the enterprise. Design/methodology/approach: This paper uses a longitudinal interpretive and exploratory case study based on semi-structured interviews, archival material and naturalistic observation at a startup enterprise in China. Findings: Focusing on the process through which shared schemata emerge to lay the foundation for routines in new firms, the authors find shared schemata emerge through a three-stage process: individual schemata emergence, partially shared schemata emergence and organizationally shared schemata emergence. Analogical transfer, strong foundational leadership and horizontal interaction among employees facilitate the development of individual schemata and their evolution into the shared schemata underlying organizational routines. Research limitations/implications: This paper contributes to the understanding of routine formation in entrepreneurial ventures by creating a framework of the stages of development of organizational routines, as well as the role management plays in each stage. This contribution fits within the emergent field of microfoundations, linking individual actions and cognition to organizational outcomes and adding to this the contribution of social interaction. Practical implications: Managers in new Chinese enterprises could benefit from understanding the importance of routinization and the managerial approaches which facilitate routine formation. This will increase the likelihood of firm survival as well as the competitive strength of the firm. Originality/value: To date, there has been little research on how routines arise in entrepreneurial ventures, and none on explicitly the role for management and interaction in fostering routinization.